KAJIAN HUKUM TERHADAP PERAN PEMERINTAH KOTA SAMARINDA DALAM PEMBERIAN BANTUAN HUKUM - Abdul Mukmin Rehas (Yuriska: Jurnal Ilmiah Hukum, 2017)
Constitution of the Republic of Indonesia Year 1945 which is the country's constitution has given recognition, guarantees, protection and legal certainty as well as equal treatment of all citizens before the law (equality before the law). In fact, the application of the principle of Equality Before The Law in Indonesia is still lacking. In the Code of Criminal Procedure (Criminal Procedure Code) only for the granting of legal aid free of charge only if the crime committed is punishable by imprisonment of 5 years or more, while if it is less than 5 years, while if the penalties are less than 5 years then the public will not get legal aid free of charge. The enactment of Law No. 16 of 2011 on the Legal Aid eliminating restrictions as stipulated in the Criminal Code, so that people can obtain legal assistance free of charge to the entire process of both the Criminal and Civil law for the sake of the implementation of the principle of Equality Before The Law.